NEWLY COMMISSIONED NAVAL OFFICER'S GUIDE - Kacher, Fred W (The U.S. Naval Institute blue & gold professional library, 2018)
"This practical guide will advise newly commissioned naval officers from all service communities in basic leadership, naval policy, service etiquette, and personal and professional administration. Using insights and writing from those who have recently made this transition, the book also serves as a gateway to the many online and print assets available to newly commissioned officers, serving as a user-friendly first stop for advice and information."--Provided by publisher